A comparative study of two groups of young adults' perceptions and attitudes toward physical discipline - Caringal, Kristine Lizette V.
ABSTRACT The study focuses on the use of Physical Discipline (PD) as a child rearing practice of Filipino families. A comparison of the perceptions and attitudes of two groups of young adults ? of ages 17-24, non-married, childless; categorized into being (1) Young Adults Physically Disciplined (YAPD) and (2) Young Adults Not Physically Disciplined (YANPD), was conducted. The 60 respondents, chosen through purposive sampling and snowball method, in a survey questionnaire showed that (1) YAPD mostly experienced being hit with an object on the buttocks, spanked on the buttocks with hand, and having talked out a problem with the parent; while the (2) YANPD mostly experienced having talked out a problem with the parent, been told of what has been done wrong, asked to think about it and select alternatives to consider for future circumstances, and had their privileges taken away from them. A Focus Group Discussion (FGD) with mixed YAPD and YANPD participants from the same sample who expressed their willingness to participate in an FGD, revealed that reasons for use of PD by parents are ? disrespect and disobedience to parents, quarreling with siblings, and ?rough house playing? causing injury to children and damage to furniture. Results of the study showed that YAPD had a positive regard towards their experienced PD, and considers mild-moderate physical disciplinary techniques to be justifiable and necessary for effecting change alongside non-physical disciplinary techniques; whereas YANPD had a negative regard towards PD, and only considers the non-physical disciplinary techniques as justifiable. However, both groups preferred non-use of physical discipline as future parents, opting to use alternative practices. Using the Chi-Square Test, it was revealed that there is no direct association between the respondents? experience of PD and its use as future parents. Thus, the present generation of young adults? negative attitudes and perceptions to the use of PD as a child rearing practice would be a key for its slowly declining use in the Filipino society.